2006
DOI: 10.1096/fj.05-4635fje
|View full text |Cite
|
Sign up to set email alerts
|

Leptin down‐regulates insulin action through phosphorylation of serine‐318 in insulin receptor substrate 1

Abstract: Insulin resistance in skeletal muscle is found in obesity and type 2 diabetes. A mechanism for impaired insulin signaling in peripheral tissues is the inhibition of insulin action through serine phosphorylation of insulin receptor substrate (Irs) proteins that abolish the coupling of Irs proteins to the activated insulin receptor. Recently, we described serine-318 as a protein kinase C (PKC)-dependent phosphorylation site in Irs1 (Ser-318) activated by hyperinsulinemia. Here we show in various cell models that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 58 publications
3
56
0
1
Order By: Relevance
“…Data of the novel PKC isoform ␦ mirrored this positive and negative modulation of insulin signaling; PKC-␦ is shown to be important for insulin-stimulated glucose uptake (36), and it participates in the insulin-dependent activation of Akt (38). On the other hand, we and others have shown that activation of PKC-␦ by lipids and leptin is involved in the impairment of insulin signaling (35,47) and in the induction of apoptosis of insulin-secreting cells (48). Serine phosphorylation of IRS-1 appears to be a major mechanism for the adverse effects of PKC-␦ on insulin action (32,41,47).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Data of the novel PKC isoform ␦ mirrored this positive and negative modulation of insulin signaling; PKC-␦ is shown to be important for insulin-stimulated glucose uptake (36), and it participates in the insulin-dependent activation of Akt (38). On the other hand, we and others have shown that activation of PKC-␦ by lipids and leptin is involved in the impairment of insulin signaling (35,47) and in the induction of apoptosis of insulin-secreting cells (48). Serine phosphorylation of IRS-1 appears to be a major mechanism for the adverse effects of PKC-␦ on insulin action (32,41,47).…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, we and others have shown that activation of PKC-␦ by lipids and leptin is involved in the impairment of insulin signaling (35,47) and in the induction of apoptosis of insulin-secreting cells (48). Serine phosphorylation of IRS-1 appears to be a major mechanism for the adverse effects of PKC-␦ on insulin action (32,41,47). Although in vitro at least 18 PKC-␦-dependent phosphorylation sites in IRS-1 have been identified (41), so far only two sites could be demonstrated to be phosphorylated in vivo and to be functional active, these are Ser 24 and Ser 318 (32,42,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, isolated adipocytes from B6 mice fed a high-fat diet showed impaired insulin-induced glucose uptake, oxidative stress and activation of PKCδ, which were suggested to be important for obesity-induced insulin resistance in the adipose tissue [28]. It has also been shown that PKCδ is involved in insulin-induced Ser-318 phosphorylation of IRS-1, thus impairing insulin signalling [29]. In this study, the role of several kinases (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…This condition is mediated by adipose-derived cytokines and hormones (among them leptin) that influence insulin action in liver, fat and skeletal muscle [26,27].…”
Section: Introductionmentioning
confidence: 99%